Primary curriculum design & delivery - Frater, Glynis (Corwin, 2023)
This is a practical guide for school leaders and teachers who have responsibility for designing and delivering a sequenced, knowledge-rich and skills-focused primary curriculum. It considers the elements that underpin a high-quality curriculum and how to create a sequential learning experience for pupils across the primary phase. It explores a range of practical tools and techniques that can support staff to build a cohesive curriculum where pupils build on their learning from year to year with high-quality outcomes for all learners, whatever their starting point. -- Provided by publisher.